2021
DOI: 10.1007/s10686-021-09725-9
|View full text |Cite
|
Sign up to set email alerts
|

A deep study of the high–energy transient sky

Abstract: The coming decades will establish the exploration of the gravitational wave (GW) Universe over a broad frequency range by ground and space interferometers. Meanwhile, wide-field, high-cadence and sensitive surveys will span the electromagnetic spectrum from radio all the way up to TeV, as well as the high-energy neutrino window. Among the numerous classes of transients, γ–ray bursts (GRBs) have direct links with most of the hot topics that will be addressed, such as the strong gravity regime, relativistic shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…High energy astrophysics has still unanswered questions mainly due to the poor sensitivity of the present instrumentation: transient events like gamma-ray bursts and in particular their X-ray afterglow emission, blazars and magnetars spectra are just a few examples of science that would benefit from higher sensitive instruments. An exhaustive review of the science that can be tackled with future focusing optics can be found in [1,2]. A substantial increase in sensitivity can be achieved by enabling hard x-ray focusing.…”
Section: -Rationale and Mission Configurationmentioning
confidence: 99%
“…High energy astrophysics has still unanswered questions mainly due to the poor sensitivity of the present instrumentation: transient events like gamma-ray bursts and in particular their X-ray afterglow emission, blazars and magnetars spectra are just a few examples of science that would benefit from higher sensitive instruments. An exhaustive review of the science that can be tackled with future focusing optics can be found in [1,2]. A substantial increase in sensitivity can be achieved by enabling hard x-ray focusing.…”
Section: -Rationale and Mission Configurationmentioning
confidence: 99%
“…SiLCs have the potential to overcome limitations imposed by the depth dose distribution, allowing the clinical use of low-energy photon beams for radiation therapy 32 (see Figure 4 for an artist impression). In high-energy astrophysics, significant efforts have been devoted to the development of focusing gamma-ray technology 28,29,[33][34][35][36][37] while work on Laue lenses for hard X-ray polarimetry is ongoing at cosine. 38…”
Section: Silicon Laue Componentsmentioning
confidence: 99%
“…Laue lenses have the potential to overcome the limitations imposed by the depth dose distribution, thereby enabling the clinical use of low-energy photon beams for radiotherapy. In high-energy astrophysics, there have been significant efforts devoted to the development of a focusing gamma-ray technology (Lund 1992, Halloin et al 2003, Frontera and von Ballmoos 2010, Barrière et al 2014, Guidorzi et al 2021.…”
Section: Silicon Laue Componentsmentioning
confidence: 99%